Studies of Metathesis for Materials Applications: Present and Future Possibilities - Marleau-Gillette, Joshua (Université d'Ottawa / University of Ottawa, 2013)
Compounds containing multiple metal-carbon bonds are now widely used as catalysts for organic and materials synthesis. Among such transformations, olefin metathesis (OM) occupies a position of pre-eminent significance. Alkyne metathesis holds great promise, but remains in a much lower state of development. The OM-directed work in this thesis sought to advance the state of the art in living, Ru-catalyzed ringopening metathesis polymerizations (ROMP). Currently, the first- and third-generation Grubbs initiators, which exhibit the ease of handling characteristic of the late metal ruthenium, dominate ROMP applications. These initiators are characterized by extremes of reactivity, however. We describe the first ruthenium initiator capable of living ROMP at RT, irrespective of monomer bulk. Polydispersity indices as low as 1.03 are routinely attainable, and excellent control is maintained in synthesis of diblock copolymers from sterically demanding and sterically unencumbered monomers. Work on alkyne metathesis sought to expand existing understanding of the features that influence stability and reactivity in ruthenium carbynes. A classification system was developed in which Class A carbynes were defined as those that readily undergo conversion into an M=C entity (e.g. vinylidene, allenylidene, or alkylidene); Class B carbynes those that have a stable carbyne functionality. Four Ru carbyne complexes, all initially regarded as prospective Class B carbynes, were selected for study. Investigation of their reactivity resulted in categorization of several as Class A species, and development of design criteria that may open the door to assembly of stable, well-defined carbyne complexes of ruthenium.
Keywords: Olefin Metathesis; Alkyne Metathesis; Ring-opening Metathesis Polymerization; Ruthenium Carbynes; Linear Pseudohalide